(7/5)y-6=-(2/3)y-(2/3)

Simple and best practice solution for (7/5)y-6=-(2/3)y-(2/3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (7/5)y-6=-(2/3)y-(2/3) equation:


y in (-oo:+oo)

(7/5)*y-6 = -((2/3)*y)-(2/3) // + -((2/3)*y)-(2/3)

(7/5)*y+(2/3)*y+2/3-6 = 0

31/15*y-16/3 = 0 // + 16/3

31/15*y = 16/3 // : 31/15

y = 16/3/31/15

y = 80/31

y = 80/31

See similar equations:

| .4y=12 | | 14k-6k+-13k+20k-18k=12 | | 5/6n=40 | | -6/5n=40 | | 10u-9u+u-u-1=9 | | -2/5x=-14.5 | | =n/2(2a=(n-1)d) | | (1-a)x=-1 | | -8×(-5/2) | | 20s-7s-17s-(-11s)-4s-(-18)=-15 | | 10x-6y=18 | | 69+4x-3= | | 7e^2x+25=20 | | 2x+34=118 | | 5+4d=1+5d | | -x^2-6x-7x=0 | | 6x^2+7y^2=42 | | -7(-2+6k)+8k=-38-8k | | -3/5u-5/2=-8/3 | | 4(-8c-3)=52 | | -53=6k+-5 | | 3x-40=80 | | 2+8x=4-5s | | -5/2=4/3x-5/4 | | -6(-5y+7)-8y=6(y-8)-8 | | 6y^2-20y+16=o | | 2.5x+2.4=2.3 | | 5(7+2b)=25 | | A=1/2-b^2 | | 41412=1.19x | | 2(a+2)=6(a-2) | | 4h-2h-h+2=11 |

Equations solver categories